3D thermo-mechanical solution of transversely isotropic and functionally graded graphene reinforced elliptical plates. (15th January 2018) - Yang, Bo; Mei, Jing; Chen, Ding; Yu, Feng; Yang, Jie
Abstract: This paper presents an analytical investigation on the thermo-elastic response of a clamped elliptical plate made of either transversely isotropic functionally graded materials (FGMs) or a novel functionally graded nanocomposite reinforced with graphene nanoplatelets (GPLs) whose weight fraction varies continuously and smoothly along the thickness direction according to three uniform and non-uniform distribution patterns. Based on three-dimensional elasticity theory and the generalized Mian and Spencer's method, 3D elasticity solutions are obtained for the elliptical plate under thermo-mechanical loading whose mid-plane displacements are constructed to satisfy the clamped boundary conditions in which the unknown constants are determined from the governing equations of the plate. The present analytical solutions are validated through comparisons with those available in open literature. A parametric study is then conducted, with a particular focus on the effects of GPL weight fraction, distribution pattern, geometry and size as well as the major to minor axis ratio of the plate on the thermo-mechanically induced stress and deformation fields.